2023
DOI: 10.4103/ajps.ajps_70_21
|View full text |Cite
|
Sign up to set email alerts
|

Bezoar Types in Children and Aetiological Factors Affecting Bezoar Formation

Abstract: Background: Bezoar is formed as a result of the accumulation of undigested food or foreign substances in the gastrointestinal tract (GIS). The present study aims to investigate the bezoar types seen in children and the aetiological factors involved in bezoar formation. Methods: A total of 16 patients who underwent an endoscopy and/or surgical treatment for bezoar at Harran University, Faculty of Medicine Pediatric Surgery Clinic between 2011 and 2019 were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our study, there were no reported psychiatric or gastrointestinal surgery histories as common risk factors for bezoar formation [ 4 , 5 , 9 ]. Dietary habits included excessive consumption of fruits or vegetables in 24.4 % of the cases and accidental ingestion of metallic objects in 17 % of the cases.…”
Section: Risk Factorsmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, there were no reported psychiatric or gastrointestinal surgery histories as common risk factors for bezoar formation [ 4 , 5 , 9 ]. Dietary habits included excessive consumption of fruits or vegetables in 24.4 % of the cases and accidental ingestion of metallic objects in 17 % of the cases.…”
Section: Risk Factorsmentioning
confidence: 96%
“…A bezoar is a concretion of indigestible foreign material in the gastrointestinal tract [ 4 ]. It can result from dietary habits, poor food digestion, overeating, gastrointestinal surgery, and psychiatric disorders [ 4 , 5 ]. Meckel's diverticulum and bezoar can both remain asymptomatic, although bezoar is known to be a precipitating factor for symptoms related to Meckel's diverticulum [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four primary types of bezoars have been described based on the nature of the forming materials, which are always non-food items taken orally, accidentally or intentionally [2,3]. Phytobezoars, the most common type, contain plant and vegetable substances, such as shells, seeds, and fruit remnants; trichobezoars are mainly composed of ingested hair; pharmacobezoars are conglomerates of medications; and lactobezoars are undigested masses of concentrated infant milk formula and mucus.…”
Section: The Nature Of Bezoarsmentioning
confidence: 99%